IoT Patient Monitoring System for COVID-19 - Kamaludin, Ummi Najwa Izzati; Ramli, Nur Ilyani (Evolution in Electrical and Electronic Engineering, 2022)
The paper is focusing in implementing the Internet of Things (IoT) in a device that monitors the vital signs of a COVID-19 patients namely the pulse rate, oxygen saturation and body temperature. The purpose of this work is to help in reducing direct contact of the medical healthcare providers with the patients and notify them if the patients need an immediate attention. This device was built via a programmable microcontroller of NodeMCU ESP8266 where the readings of the vital signs collected by the sensors will be uploaded to cloud so the readings can be displayed on the via Blynk application and the hardware developed simultaneously. The sensors that are involved in collecting the body temperature is MLX90614 and pulse oximeter sensor MAX30100 for pulse rate and oxygen saturation. The medical staffs will receive alert notification on three situation which is when the pulse rate more than 100 BPM, oxygen saturation in blood (SpO2) less than 94% and the body temperature that is 39°C and above. The data obtained shows that the vital signs are accurate when being compared to the product existed in the market. Hence, it can be used in reducing the risk on the healthcare providers from being infected and in the development of the healthcare services. Further possible attempt may include the use of microcontroller with wider range for the medical staff’s accessibility.